2008
DOI: 10.1590/s0100-879x2008001200012
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and body composition after 6 months of patients switching from continuous ambulatorial peritoneal dialysis to automated peritoneal dialysis

Abstract: Our objective was to determine if automated peritoneal dialysis (APD) leads to changes in nutritional parameters of patients treated by continuous ambulatory peritoneal dialysis (CAPD). Twenty-six patients (15 males; 50.5 ± 14.3 years) were evaluated during CAPD while training for APD and after 3 and 6 months of APD. Body fat was assessed by the sum of skinfold thickness and the other body compartments were assessed by bioelectrical impedance. During the 6-month follow-up, 12 patients gained more than 1 kg (GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The LW group had a reduction in fat mass (FM) and body cell mass (BCM). In the GW group, FM and BCM increased [ 82 ]. One study followed up PD patients for 1 year, and found that in the GW group, the increase in FM was the most obvious, while all components in the LW group decreased simultaneously, including intracellular water (ICW), extracellular water (ECW), fat mass (FM), body protein volume (BPV), and bone mineral content (BMC) [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LW group had a reduction in fat mass (FM) and body cell mass (BCM). In the GW group, FM and BCM increased [ 82 ]. One study followed up PD patients for 1 year, and found that in the GW group, the increase in FM was the most obvious, while all components in the LW group decreased simultaneously, including intracellular water (ICW), extracellular water (ECW), fat mass (FM), body protein volume (BPV), and bone mineral content (BMC) [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six months after the start of peritoneal dialysis (PD), the patient’s phase angle (PhA) decreased significantly [ 82 ]. However, one study showed that PhA in the PD group was higher than that in the CKD5 group before dialysis [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Williams et al 20 found no proof that PD patients are more obese than those on HD, and -what is more important -that obesity of dialysis patients is not correlated with increased risk of getting CVD for the general population. On the contrary, low BMI and other parameters of underfeeding were strong independent indicators of mortality for dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the LW group had a reduction in fat mass (FM), body cell mass (BCM). In the GW group, FM and BCM were increased [82]. One study followed up PD patients for 1 year, and found that in the GW group, the increase of FM was the most obvious, while all components in the LW group decreased simultaneously, including intracellular water (ICW), extracellular water (ECW), fat mas (FM), body protein volume (BPV), and bone mineral content (BMC) [83].…”
Section: Peritoneal Dialysis 1) Lean Tissue and Fatmentioning
confidence: 99%
“…Six months after the start of peritoneal dialysis (PD), the patient's phase angle (PhA) decreased significantly [82]. However, one study showed that PhA in PD group was higher than that in CKD5 group before dialysis [43].…”
Section: ) Phase Anglementioning
confidence: 99%